Remote teaching: Methods, tools and technologies - Nadda, J.B., Singh, A.K. and Jain R. (University News)
Due to worldwide outbreak of unforeseen Covid-19, all walks of life seem to have been affected. Educational sector also could not stay unaffected but the same cannot be said about technology, therefore usage of technology (ICT) in imparting education in the form of online education is not only the most talked about theme recently but also the most explored area. This can be understood by the fact that search for online learning and remote teaching-learning phrases has increased significantly from the mid of March 2020 according to Google Trends (2020)1 .- Reproduced
Keywords: Online teaching, Covid 19, Education